The main Portuguese SAD's: comparative study between the economic and financial viability and the success of their sports clubs - Silva, M. (2016)
The object of this paper is to assess the profitability of the four leading Portuguese Sociedades Anónimas Desportivas (SADs)1 by comparing the economic and financial data of each SAD with the respective sports results of the clubs attached to these SADs. The methodology followed the various steps inherent to this type of paper, all the while adopting both a qualitative and quantitative approach, i.e. a hybrid approach. Initially, we took on an interpretative paradigm, as the elements necessary for research arise from the observation and analysis of data. We began by increasing our scientific knowledge on the subject of analysis: SADs, sports results and balanced financial structures. This was followed by a characterisation of the sector and a thorough analysis of both the accounts and the sports results of the SADs and the clubs. Thereafter, we crossed the data from these two analyses and completed the project with a number of key measures to achieve both financial and sporting success. Finally, it was possible to conclude that a Sociedade Anónima Desportiva can, in fact, achieve satisfactory economic, financial and sporting levels if a number of guiding principles are adopted. Principles that, when interconnected through a virtuous cycle, generate greater revenue and consequently profits, contributing to a balanced financial structure, conducive to more victories and naturally titles, which in turn provide increased revenue, thereby bestowing coherence to the virtuous cycle.